2017
DOI: 10.1080/21691401.2017.1365723
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal and pupicidal evaluation of silver nanoparticles synthesized using Aquilaria sinensis and Pogostemon cablin essential oils against dengue and zika viruses vector Aedes albopictus mosquito and its histopathological analysis

Abstract: Mosquitoes pose a threat to humans and animals, causing millions of deaths every year. Vector control by effective eco-friendly pesticides of natural origin is a serious issue that requires urgent attention. The employment of green-reducing extracts for nanoparticles biosynthesis in a rapid and single-step process represents a promising strategy. In this study, silver nanoparticles (AgNPs) were biofabricated using an essential oil of Aquilaria sinensis (AsEO) and Pogostemonis Herba essential oil of Pogostemon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 48 publications
(59 reference statements)
4
26
0
5
Order By: Relevance
“…The appearance of light brown color was caused by the excitation of surface plasmon vibrations in silver nanoparticles [27] at 415 nm, which predicted the formation of AgNPs. Previous reports have shown evidence that similar color changes caused the agitation of the Surface Plasmon Resonance (SPR) peak of the synthesized AgNPs [15,21,32]. The maximum absorption peak of ZEO-AgNPs was found at 415 nm, which indicates the fabrication of AgNPs [33,34,35].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The appearance of light brown color was caused by the excitation of surface plasmon vibrations in silver nanoparticles [27] at 415 nm, which predicted the formation of AgNPs. Previous reports have shown evidence that similar color changes caused the agitation of the Surface Plasmon Resonance (SPR) peak of the synthesized AgNPs [15,21,32]. The maximum absorption peak of ZEO-AgNPs was found at 415 nm, which indicates the fabrication of AgNPs [33,34,35].…”
Section: Discussionmentioning
confidence: 74%
“…The silver nanoparticles (AgNPs) were synthesized by the essential oil reduction method of Ga’al et al [21] with some modification. The C. zedoaria essential oil (ZEO) was used as both a stabilizing and reducing agent.…”
Section: Methodsmentioning
confidence: 99%
“…[18] Smelling a unique woody odor, the essential oil of P. cablin, usually known as patchouli oil, is of great industrial importance [19] and has been reported showing bioactivities against insect pests. There are some reports recording the insecticidal activities of P. cablin against mosquito vectors, [20] cockroach, [21] termites, [22,23] armyworm, [24] and ants, [25,26] as well as repellent effects on termites, [22,23] sweetpotato whitefly, [27] urban ants [25] and the cockroach. [21] And a recent paper [26] reported that P. cablin essential oil showed behavioral impairment on leaf-cutting ants.…”
Section: Introductionmentioning
confidence: 99%
“…Positive charge, acidic environment of midgut, and nanosize of silver particles are suitable for easy internalization and mucoadhesion of the above-discussed AgNPs in insect gut (Jiang et al 2015). Silver nanoparticle-treated larvae of A. albopictus revealed severe lesions in midgut epithelium layer including vacuolization of the cell, degradation of the membrane, broken brush border, rupture of cells, cytopathological variations, destruction of epithelial cells, and degradation of nuclei (Ga'al et al 2018). Similar effects, such as apical swelling in the midgut, reduction of intracellular contact within cells, and degeneration of nuclei were also observed in A. aegypti after treatment of Hedychium coronarium Koenig rhizome-derived AgNPs (Kalimuthu et al 2017b).…”
Section: Impact On Midgut Reproduction and Development Under Npsmentioning
confidence: 99%